Health behaviour among parents of overweight and obese children - Małgorzata Kołpa; Beata Jurkiewicz; Joanna Norek (University of Applied Sciences in Tarnow, Poland, 2017)
Introduction: The period of puberty is especially important in the shaping of behaviours with respect to adequate diet and physical activity. Habits established during this period are repeated later in life. Aim of the study: The purpose of the thesis was to determine the extent of influence of parents' health behaviour on the physical activity of children with an excess body mass problem. Material and methods: The research was conducted in the period from November 2015 to March 2016 at the University Children's Hospital of Cracow among 88 parents whose children suffer from overweight and obesity. For this purpose, the research used the diagnostic survey method and the measurement method (body mass and height). The research tools included the Health Behaviour Inventory (HBI) by Juczyński, an authorial survey questionnaire, an anthropometer and the Tanita BF350 scales. Basic descriptive statistics were used to describe the results, the differences between variables were verified using the χ2 test of independence. The materiality level was assumed to be p<0.05. Results: As many as 32 parents of children with excess body mass (36.36%) were overweight as well, while 28 (31.82%) kept their body mass within the norm. A large proportion of the respondents, 33 parents (37.50%), stated that it was not customary to do sports in their family, and less then a half of the children (n=36; 40.91%) regularly participated in physical education classes. Children of the parents whose BMI was normal participated in physical education classes significantly more often than children of the other parents (p<0.001). The average number of points obtained by the respondents in the HBI questionnaire equals 70.81 (SD=22.41 pp). Parents rated their health behaviour the highest on the "positive psychical attitude" subscale (avg. 18.01; SD=5.77 pp), and the lowest on the "health practices" subscale, which includes e.g. physical activity (avg. 17.24; SD=6.21 pp). Conclusions: Health promoting activities shaping health behaviours should be performed by schools, with an active participation of parents. It is necessary to carry out educational programmes in the area of adequate nutrition and physical activity, which would expand knowledge of the problem.